Penetapan Harga Pokok Produksi Dengan Metode Full Costing Sebagai Dasar Penentuan Harga Jual Kain Tenun Songket Melayu - Dariana Dariana (LPPM ISNJ Bengkalis, 2020)
Songket Melayu weaving craftsmen in determining the cost of production as the basis for determining the selling price are still inaccurate because they are based on estimates and have not classified costs in the calculation of the cost of production. This study aims to assist in determining the cost of goods manufactured as a basis for determining the selling price using the full costing method. This research is descriptive qualitative research. The results of this study indicate the difference in the cost of production between the weaving craftsmen's calculations with the full costing method. The result of the calculation of the cost of production according to the weaving craftsman is IDR 483,333.33 per piece, while the full costing method is IDR 528,833.00 per piece. The difference in production costs is IDR 45,500.00 lower than using the full costing method. The determination of the selling price of the product is based on the cost of goods sold per piece of woven fabric plus the desired profit of the company of 35% in order to cover the production costs that have been incurred. The result of the calculation of the selling price according to the weaving craftsman is IDR 113,925.00 per piece lower than using the full costing method.